Combined therapy of undifferentiated carcinoma of nasopharyngeal type - Došen, Danijel (Radiology and oncology (Ljubljana), 1997)
From November 1989 to October 1993, 339 patients with stage IV undifferentiated carcinoma of nasopharyngeal type (UCNT) were enrolled in a randomized trial comparing neoadjuvant chemotherapy (cisplation, epirubicin, bleomycin - BEC) plus radiotherapy (171 patients) vs. radiotherapy alone (168 patients). All patient characteristics were well-balanced in both arms. The overall response rate assessed clinically by the investigator at the end of chemotherapy was 91% (WHO) with 47% CR and 4% PR. Three months after the completion of radiotherapy, a CR (clinical + CT scan) was observed in 55% of the combined treatment group compared to 34% in the radiotherapy-alone group (p<0.01). Tumor recurrence or progression was observed in 55/171 patients in the chemotherapy arm (32.7%), compared to 92/168 patients in the radiotherapy-alone arm (54.7%) (p<0.01). In conclusion, the addition of BEC type chemotherapy, has changed the proportion of UCNT patients continously disease free but the overall survival data are not yet mature.
Keywords: Drug therapy; Nasopharyngeal neoplasms; Radiotherapy; Survival analysis